Lessons learned from a generation of community-driven business retention and expansion programming. Issue 2 (15th March 2017) - Darger, Michael; Tuck, Brigid; Bennett, John
Abstract: Business retention and expansion (BRE) can strengthen the economic and social fabrics of communities when led by a broad cross section of community leaders and supported by professionals skilled in BRE process techniques. This article explains lessons learned from a generation of broad-based BRE visitation initiatives facilitated by the University of Minnesota Extension. Two program improvements, their genesis, and outcomes are featured. The first improvement stemmed from a comprehensive review of nine community BRE initiatives in which the results had not been reported as either successful or unsuccessful. The second improvement is the application of a consistent evaluation rubric: ripple effect mapping . The article demonstrates that (1) volunteer involvement in BRE can be effective in creating community-wide benefits and (2) there are benefits to striving for both community development and economic development through BRE. Thus, BRE can be effective for community improvement overall, not just for jobs and economic impact.